HOW CULTURE SHAPES LANGUAGE: A CROSS-CULTURAL PERSPECTIVE - Rattiel, M. (International Journal of Literature and Language Studies, 2023)
This study investigates the profound influence of culture on linguistic development by analyzing vocabulary, idiomatic expressions, and sociolinguistic norms. It posits that language is not merely a tool for communication but a reflection of a communitys shared values, historical experiences, and social hierarchies. Furthermore, the research examines the impact of rapid globalization and digital transformation on linguistic evolution, highlighting the tension between lexical innovation and the risk of language attrition. These findings underscore the necessity of cultural context in linguistic analysis and offer critical insights for enhancing intercultural competence in an interconnected world.